UKRAINE IN THE CONTEXT OF THE GLOBAL URBAN PROCESSES - Anastasiia Mazurova (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2015)
The general characteristic of the global urban processes was presented in the article. Dynamics of urban saturation in Ukraine and the world and structure of urban and rural population for some years in Ukraine was analyzed. The features of global historical development of megalopolises were defined. Classification of the worldwide cities according to United Nations Human Settlements Programme and the characteristic of the Ukrainian cities on this classification was presented. Dynamics of number of the Ukrainian cities and urban saturation of regions of Ukraine was analysed. The highest and the lowest urbanized state regions in Ukraine were revealed.